The black heavens : Abraham Lincoln and death - Dirck, Brian R., 1965- (Southern Illinois University Press, 2019)
"Drawing upon extensive recent historical studies regarding death, funerals, and mourning during the Civil War era as well as primary sources, The Black Heavens provides a realistic view of Lincoln as he encountered death. Avoiding the sentimentalization and excessive psychoanalyzing that has characterized much of the historical (and fictional) writing on the subject, this book carefully situates Lincoln within the social, cultural, and political contexts of death and mourning in his time"--